Inside the mind of the serial murder - Holmes, Ronald M. (American journal of criminal justice, 1988)
This article approaches a position of delving into the thoughts of those who commit murder serially. The information comes from a variety of sources which include research literature, theory examination and most importantly, serial murderers themselves. More than 400 cases of serial fatal violence as well as interviews with incarcerated serial killers were utilized. Important issues such as locus of motives, expected gains, victim selection processes, planning of the event, the murder event itself, and organization and disorganization of the kill are also discussed. While admitting that serial killers have never been rehabilitated, a call is directed toward a better understanding of the mind of the serial murderer.